Karakteristik Metode Tafsir Al-Quran Secara Holistik (Studi Literatur) - Farid, Ahmad; Daniati, Putri; Noor, Rachmah; Nuryeni, Nuryeni; Zuhrufa, Armalia Putri; Febiana, Riska; Aulia, Rahma; Aulia, Tsabita (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims at various methods that can be used in the interpretation of the Quran. This research involves extensive qualitative analysis of the existing literature. Its main purpose is to conduct a comprehensive review and explanation of available information by referring to a variety of sources. The main objective of this qualitative literature review is to collect, evaluate, and synthesize existing knowledge regarding a particular topic, with a particular focus on the characteristics and qualities of the Quran. The data collection process includes careful textual analysis, data retrieval, and systematic organization of information. The results of data analysis show that the Qur'an as kalamullah has the highest and noblest position as a guide to human life. Efforts to understand the meaning of the verses of the Qur'an are called tafsir, certainly according to the limits of the ability of each scholar, because it is impossible to explore and extract the meaning of the verses of the Qur'an with absolute truth. There are various methods that can be used in interpreting the Quran including the maudhui' (thematic) method, tahlīliy method, ijmāliy, muqāran are still widely used today by modern mufassir, including Indonesian mufassir